Mapping mismatches : English-medium education policy, perceptions and practices in the low-fee private schools in Quetta Pakistan / Syed Abdul Manan - Manan, Syed Abdul (2015)
Pakistan is a multilingual and multi-ethnic country whereby English is the official language and Urdu is the national language. It has five different school systems, which operate in parallel and practice different media of instruction. Such different school systems reflect the various socio economic status of the students. Consequently, this study focuses on the low-fee English-medium private schools that cater to children largely from low-income backgrounds. The number of low-fee schools has exponentially proliferated over the last two decades, almost ten-fold as estimates suggest. One out of three school-going children attends private schools. Low-fee schools use an English language curriculum and advertise themselves as English-medium, which motivates parents from low-income families to enrol their children wanting them to learn English because it is the ‘passport to privileges’. This study examines the straight-for-English policy these schools adopt, although, researchers in bi/multilingual education propose a mother-tongue based policy at primary level, a language familiar to children, the one to which they have maximum exposure in their social environment. The study addressed three aspects of the policy: perceptions of stakeholders about straight-for-English policy, English-teaching and learning practices and children’s exposure to English. Employing a mixed methodology involving questionnaires, interviews, observations and field notes, the study surveyed 11 schools in Quetta city, Pakistan. The respondents consisted of 245 students from high-secondary classes, 8 teachers, 11 school principals, and 9 expert observers. The study used mixed methodology with a triangulation research design. Two different perceptions emerge from the data where students, teachers and school principals strongly endorse the current straight-for-English policy presuming that the earlier the child gets exposed to the English language, the better. However, language policy experts express concerns over straight-for-English policy and recommend mother tongue based multilingual policy. They propose that the formulation of the medium of instruction policy must be contextualized considering theory, research, available human resources, and the sociocultural and socioeconomic realities of children. The current policy can be elusive and ill-informed as it does not take into account any of the above conditions. In practice, English is not used meaningfully and substantively in classroom transactions, which can be helpful in learning the language as purported in policy and presumed by supporters of the policy. In fact, teachers use Urdu language to teach English. On the other hand, reading practice is usually a chorus repetition, while writing is limited to copying from textbooks and examination is rote-learning based. As a result, the writing ability of students stands below average. The children learn a translated bookish English with no communicative potential; their learning of content is imitative, not interpretive and the use of English can be symbolic and pretentious. Belonging predominantly to illiterate and semi-literate parental backgrounds, barring a negligible number, vast majority of children have no exposure to English at home. The study concludes that straight-for-English policy needs to be reviewed as it suffers from mismatches in terms of theory, practice and sociocultural landscapes of students. It might be better if children are taught in their mother tongues at least in the primary level.